A Study on the Prevalence and Subtype Diversity of the Intestinal Protist Blastocystis sp. in a Gut-Healthy Human Population in the Czech Republic - Lhotská, Zuzana (Front Cell Infect Microbiol, 2020)
Blastocystis sp. is a common intestinal protist colonizing the human intestine the prevalence of which varies across non-industrialized and industrialized countries. Its role in the human gut ecosystem remains unclear due to persisting gaps in knowledge of epidemiology and factors affecting gut colonization. Here, we aimed to expand the knowledge of the epidemiology of Blastocystis sp. in the gut-healthy humans in one of the industrialized European countries, including the distribution of its subtypes, the correlation between its occurrence and several factors such as lifestyle, contact with animals, age, and sex. A total of 288 stool samples were obtained from asymptomatic individuals over the entire age-range and 136 samples from animals with which the volunteers were in frequent contact. All samples were examined in parallel by PCR and xenic in vitro culture. Blastocystis sp. was detected in samples from both human and non-human hosts. In humans, the overall prevalence was 24% and eight subtypes were found; in animals, the prevalence was 10%, and only five subtypes were detected. A higher incidence of Blastocystis sp. was observed in individuals (i) traveling outside Europe, (ii) in frequent contact with livestock, and (iii) over 50 years of age. We found no effect on gender on Blastocystis sp. colonization. SUMMARY: This study provides data on the prevalence and diversity of the gut protist Blastocystis sp. and its subtypes in a gut-healthy human population with emphasis on several factors such as contact with animals, lifestyle, age, and gender.